The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1365-2672.2002.01721.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and number of Salmonella in sausages and their destruction by frying, grilling or barbecuing

Abstract: Aims: To determine the prevalence and number of Salmonella and Campylobacter in sausages and to evaluate their destruction during cooking. Methods and Results: One hundred and sixty-two packs of uncooked economy or catering sausages, comprising 53 packs of frozen and 109 of chilled sausages, were purchased in Devon between March and July 2000. All were tested for the presence of Salmonella and 51 packs of chilled sausages were also examined for the presence of Campylobacter spp. To investigate the heat toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 7 publications
2
22
0
3
Order By: Relevance
“…According to Mattick et al (2002), one of the main problems in the isolation of Salmonella in foods is the small number of these bacteria considering the rate of bacterial contamination. According to Bennett et al (1998), the BAX® system always produced a positive result when the cell count of Salmonella spp.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…According to Mattick et al (2002), one of the main problems in the isolation of Salmonella in foods is the small number of these bacteria considering the rate of bacterial contamination. According to Bennett et al (1998), the BAX® system always produced a positive result when the cell count of Salmonella spp.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…Our results were similar to those obtained by Seydi and Sylla (1996) in Dakar, but were clearly inferior to those of Elhag et al (2014) in Khartoum who revealed that 97.5% of the studied sausage samples were contaminated by these bacteria. Many studies showed than the Salmonella can be isolated from various types of sausages (Abrahim et al, 1998;Mattick et al, 2002;Özbey et al, 2007). The high incidence of these bacteria could be due to the faeces contamination of the chopped meat used for the production of pork-butchery, contaminated water, the environment and bad hygiene of workers (Reid et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The four-strain composite culture was used to inoculate various substrates in order to prepare the inocula under representative environmental conditions (inoculum origin). The control inoculum (TSB) was obtained by inoculating (5 log CFU/ml) TSB-G with the composite E. coli O157:H7 culture (1 ml), and, after overnight incubation at 35°C, the resulting cell suspension was diluted (1,000-fold) in sterilized maximum-recovery diluent (MRD; 1.0 g peptone [Difco] and 8.5 g sodium chloride [Fisher Scientific, Fair Lawn, NJ] in 1 liter distilled water) (18).…”
Section: Methodsmentioning
confidence: 99%